2016
DOI: 10.1073/pnas.1600614113
|View full text |Cite
|
Sign up to set email alerts
|

Knotting and unknotting of a protein in single molecule experiments

Abstract: Spontaneous folding of a polypeptide chain into a knotted structure remains one of the most puzzling and fascinating features of protein folding. The folding of knotted proteins is on the timescale of minutes and thus hard to reproduce with atomistic simulations that have been able to reproduce features of ultrafast folding in great detail. Furthermore, it is generally not possible to control the topology of the unfolded state. Single-molecule force spectroscopy is an ideal tool for overcoming this problem: by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 59 publications
7
101
2
Order By: Relevance
“…Recently, optical tweezers were used on UCH-L1 to take it to three different unfolded states: unknotted, 3 1 -and 5 2 -knotted and refolding from such states was measured [61]. This study showed that threading to form either a 3 1 -or 5 2 -knotted state slowed folding as expected.…”
Section: Complex Knotted Proteins: Uchs and Dehimentioning
confidence: 58%
“…Recently, optical tweezers were used on UCH-L1 to take it to three different unfolded states: unknotted, 3 1 -and 5 2 -knotted and refolding from such states was measured [61]. This study showed that threading to form either a 3 1 -or 5 2 -knotted state slowed folding as expected.…”
Section: Complex Knotted Proteins: Uchs and Dehimentioning
confidence: 58%
“…Their unique domain architecture – a single domain that binds to and hydrolyses the isopeptide bond of ubiqutinated substrates – with very slow off-rates for releasing hydrolysed ubiquitin products39 potentially increase the likelihood of encountering the proteasome machinery that actively unfolds ubiquitinated substrates for degradation. Indeed, it has been suggested by the recent single molecule mechanical unfolding study of UCH-L1 that the mechanical stability of the UCH domain may be beneficial for resisting UPS degradation40. Another important finding from the single molecule study is the consistent timescale of refolding triggered from mechanically and chemically unfolded states, implying that the intrinsic unfolding rates in the absence of chemical denaturant can be reliably derived from extrapolation of the linear dependency of chemical denaturant concentration (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In either case, a simple protocol could consist in mutating into cysteine both residues at the ends of an entangled loop, provided no other cysteines are present in the sequence, and in assessing whether the folding is then hindered by the formation of a disulfide bridge in oxidizing conditions. In the context of knotted proteins, single molecule force spectroscopy techniques were shown to be particularly useful in controlling the topology of the unfolded state [46]. Similarly, both "in vivo" folding experiments [47] and appropriate simulation protocols [48][49][50] could be employed to test the possible role of cotranslational folding in determining the patterns detected for entangled motifs: double cysteine mutants would then be predicted to be more deleterious for the folding of C-terminal threads with respect to N-terminal threads.…”
Section: Discussionmentioning
confidence: 99%